2016
DOI: 10.1177/1352458516652498
|View full text |Cite
|
Sign up to set email alerts
|

Altered intestinal permeability in patients with relapsing–remitting multiple sclerosis: A pilot study

Abstract: The relatively high proportion of IP changes in RR-MS patients seems to confirm our work hypothesis and warrants more work to confirm the result on a larger sample, and to understand the implications for related immunological disturbances and intestinal microbiota alterations. Our finding may also have relevance for oral treatments, recently introduced in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 20 publications
1
80
0
3
Order By: Relevance
“…For instance, Buscarinu et al . recently demonstrated that there is an increase in intestinal permeability along with a reduction in intestinal absorption in patients with the relapsing/remitting form of the condition . A separate clinical study identified an increase in circulating LBP in patients with relapsing/remitting multiple sclerosis, potentially indicating an increase in the translocation of Gram‐negative bacteria from the intestinal lumen to the circulation .…”
Section: Microbiota and Neurology: Aging And Neurodegenerationmentioning
confidence: 99%
“…For instance, Buscarinu et al . recently demonstrated that there is an increase in intestinal permeability along with a reduction in intestinal absorption in patients with the relapsing/remitting form of the condition . A separate clinical study identified an increase in circulating LBP in patients with relapsing/remitting multiple sclerosis, potentially indicating an increase in the translocation of Gram‐negative bacteria from the intestinal lumen to the circulation .…”
Section: Microbiota and Neurology: Aging And Neurodegenerationmentioning
confidence: 99%
“…46 Validated algorithms such as Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) 47 can be employed to enable metagenomic predictions from 16S rRNA sequencing data, allowing inferences to be made about the potential functional capacity of the microbiota in neurological conditions. 64 Differences in the Gut Microbiota between MS Cases and Healthy Controls Studies are emerging involving both adult and pediatric MS subjects (Supplementary Table). 50 The Microbiome and Neuroimmune Conditions MS Compelling evidence for the microbiome's role as either a trigger of neuroimmune disease or a driver of neuroimmune disease activity has largely emerged from animal models of MS (reviewed elsewhere 51,52 ).…”
Section: What Are They Doing? Functionality Of the Microbiotamentioning
confidence: 99%
“…62,63 An increased prevalence of "leaky gut" (measured via an oral lactulose/mannitol test) was also recently suggested in a pilot study of 22 relapsing-remitting MS cases compared to controls. 64…”
Section: Msmentioning
confidence: 99%
“…Observational studies have found increased intestinal permeability in MS, which might be an effect of the altered microbiome. 55 Levels of LPS in the circulation (a marker of intestinal permeability) are associated with increased serum IL-6 and IL-17 levels, and correlate with Expanded Disability Status Scale scores. 23 LPS can reduce BBB integrity by inducing expression of leukocyte adhesion molecules that bind to receptors upregulated in CNS inflammation, and can activate phagocytes in the parenchyma.…”
Section: Additional Host-microbiome Interactionsmentioning
confidence: 99%